Ultralong C(sp3)–C(sp3) Single Bonds Shortened and Stabilized by London Dispersion - Shimajiri, Takuya; Kawakami, Yuta; Kawaguchi, Soki; Hayashi, Yuki; Hada, Kazuto; Suzuki, Takanori; Ishigaki, Yusuke (Synlett, 2022)
A carbon–carbon (C–C) single bond longer than 1.7 Å shows unique bond flexibility, even though a C–C single bond is typically rigid and robust. We report here that the bond length of flexible C–C single bonds surrounded by bulky alkyl groups in novel hexaphenylethane-type hydrocarbons might be affected by weak noncovalent interactions, such as London dispersion. Thanks to London dispersion, an ultralong and flexible C–C single bond exhibits an obvious bond contraction. X-ray analyses and Raman spectroscopy provided direct information regarding the bond length and strength, whereas density functional theory calculations explained the bond contraction driven by London dispersion. The change in bond length of an extremely elongated flexible C–C bond would be a good probe for quantifying weak interactions that are usually difficult to detect.
Keywords: strained molecules; hydrocarbons; C–C bond length; X-ray analysis; London dispersion